2016
DOI: 10.1038/srep35256
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors in mouse anterior piriform cortex initialize early odor preference learning and L-type calcium channels engage for long-term memory

Abstract: The interactions of L-type calcium channels (LTCCs) and NMDA receptors (NMDARs) in memories are poorly understood. Here we investigated the specific roles of anterior piriform cortex (aPC) LTCCs and NMDARs in early odor preference memory in mice. Using calcium imaging in aPC slices, LTCC activation was shown to be dependent on NMDAR activation. Either D-APV (NMDAR antagonist) or nifedipine (LTCC antagonist) reduced somatic calcium transients in pyramidal cells evoked by lateral olfactory tract stimulation. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…∆FOSB cell counts were acquired from 18 relevant brain regions (see Table 1 ) from 3–6 sections from each animal. The piriform cortex (Pir), an olfactory processing region 60 , was included due to its expected lack of involvement in CSDS. Exclusion criteria for single cell count data points was a deviation of ≥3 times the interquartile range below or above the median of the group.…”
Section: Methodsmentioning
confidence: 99%
“…∆FOSB cell counts were acquired from 18 relevant brain regions (see Table 1 ) from 3–6 sections from each animal. The piriform cortex (Pir), an olfactory processing region 60 , was included due to its expected lack of involvement in CSDS. Exclusion criteria for single cell count data points was a deviation of ≥3 times the interquartile range below or above the median of the group.…”
Section: Methodsmentioning
confidence: 99%
“…In the hippocampus, LTCCs mediate protein synthesis sensitive, NMDAR-independent late phase LTP and spatial learning (Grover and Teyler 1990;Moosmang et al 2005). However, in the aPC, we have shown that LTCC activation is dependent on NMDAR activation and both channels play critical but distinct roles in the early odor preference learning (Mukherjee and Yuan 2016). Here either D-APV or nifedipine blocked isoproterenol induced learning (Fig.…”
mentioning
confidence: 74%
“…1C). The larger portion of the LTCC current in P7-10 pups correlates with a highly plastic period in which LTCC-dependent early odor preference learning occurs (Jerome et al 2012;Mukherjee and Yuan, 2016). Figure 2A and B demonstrated effects of isoproterenol on the whole-cell calcium currents in the two age groups.…”
mentioning
confidence: 93%
“…Using calcium imaging in aPC slices, Mukherjee and Yuan ( 2016 ) demonstrated that LTCC activation is subsequent to NMDAR activation. Behaviorally, it was shown that LTCCs are required for early odor preference LTM but STM can still occur without LTCC activation.…”
Section: Ltcc In Olfactory Learningmentioning
confidence: 99%
“…LTM requires PKA-activated CREB signaling as it is both protein synthesis and transcription dependent (Yuan et al, 2003 ; McLean et al, 2005 ; Grimes et al, 2011 ). Owing to their location in the somatic membrane and at the base of the apical dendrite (Mukherjee and Yuan, 2016 ), LTCCs could be a fit candidate to bridge synaptic excitation and provide necessary calcium to the soma, activating kinases which subsequently phosphorylate CREB to initiate transcription in the nucleus and ultimately protein synthesis. Activation of LTCCs following NMDAR activation in the aPC is consistent with this hypothesis (see Figure 1 ).…”
Section: Ltcc In Olfactory Learningmentioning
confidence: 99%